2017
DOI: 10.1109/tasc.2017.2666142
|View full text |Cite
|
Sign up to set email alerts
|

Progress on the Development of the Nb3Sn 11T Dipole for the High Luminosity Upgrade of LHC

Abstract: Abstract-The High Luminosity LHC Project at CERN entered into the production phase in October 2015 after the completion of the design study phase. In the meantime, the development of the 11 T dipole needed for the upgrade of the collimation system of the machine made significant progress with very good performance of the first two-in-one magnet model of 2-m length made at CERN. The 11 T dipole, which is more powerful than the current main dipoles of LHC, can be made shorter with an equivalent integrated field.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…The single-and two-in-one-aperture structures developed at CERN for the 11 T dipole (Savary et al 2017) are shown in Fig. 9.9.…”
Section: Short Dipole Modelsmentioning
confidence: 99%
“…The single-and two-in-one-aperture structures developed at CERN for the 11 T dipole (Savary et al 2017) are shown in Fig. 9.9.…”
Section: Short Dipole Modelsmentioning
confidence: 99%
“…Nowadays, the new LHC luminosity upgrade [3], [4] has required the development of two new superconducting magnets wound with Nb3Sn superconductor: the 11 T dipole for the arcs [5] and the MQXF quadrupole for the insertion regions [6]. These two projects are already well advanced in the prototyping phase, after having gone through a short model development program [7], [8]. At the moment of writing this paper, a total of 17 model coils have been produced for each of the projects.…”
Section: This Work Was Supported By the High Luminosity Lhc Project Amentioning
confidence: 99%
“…With respect to the LHC, this quest for a doubling of the field requires a change of superconducting material, because the upper critical field B c2 of Nb-Ti at 1.9 K is limited to, at most, 13.5 T (Bottura 2000), limiting the ultimate field amplitude of Nb-Ti accelerator magnets to about 10 T. A field level of 16 T is also 5 T higher than the field in the Nb 3 Sn magnets currently being developed for the High Luminosity LHC (HL-LHC or Hi-Lumi LHC) Savary et al 2017). Once installed, they will be the first high-field Nb 3 Sn magnets ever operated in a particle collider.…”
Section: Introductionmentioning
confidence: 99%